The Holiday Effect in Stock Markets - Wanxin, Pang (International Journal of Psychosocial Rehabilitation, 2020)
This paper reviews the literature on the holiday effect, the "holiday effect" caused by the upsurge of consumer enthusiasm for the relevant industries to bring out a seasonal increase in earnings. In this context, the stock market also shows abnormal price fluctuations pre-holiday and post-holiday, namely the "holiday effect" of the stock market. After reviewing the literature on holiday effects all over the world, we then found that no matter if developing countries or developed countries, they almost all have an existing holiday effect. Two, some of the holidays are affected by culture, and some are non-culture. Last, most of the scholars examined some main index when doing research. Actually, the sector index is also very important in the research.